Redeeming Justice - Carter, Terrell (2021)
Approximately three decades ago, two of us, Terrell Carter and Kempis Songster, were sentenced to life in prison without the possibility of parole. The U.S. Supreme Court has said that this sentence, effectively an order to die in prison, represented a legal determination that we were irredeemable. In this Article, with insights from our coauthor and friend, human rights scholar Rachel López, we ask: What does it mean for the law to judge some human beings as incapable of redemption? Isn’t the capacity for change core to the human condition, and shouldn’t that be reflected in the law? This Article marries human rights law with our lived experience to argue that the capacity for redemption is an innate human characteristic. By documenting the dehumanizing effect of codified condemnation and the struggle for humanity after a person has been found irredeemable in a court of law, we seek to show why all humans should have a legal right to redemption—a right embedded in the Eighth Amendment through the latent concept of human dignity. The reading of the Eighth Amendment we call for would require a dramatic reimagination of the U.S. criminal legal system into one that elevates humanity, not deprives it. One that creates the opportunity for healing and human development, not denies it. One that facilitates the human capacity for redemption, not forbids it. One, in other words, that recognizes that change is always possible. Redeeming justice thus requires that legal systems not make unalterable decisions about a human being’s capacity for change. At a bare minimum, this means that all sentences should be reviewable, with release possible after someone redeems herself. No person should be permanently deprived of her hope for freedom